2018
DOI: 10.1007/s40167-018-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Mine or mother’s? Exploring the self-ownership effect across cultures

Abstract: In exploring self-biases in cognition and decision-making, recent research has demonstrated cultural variation in the emergence of the self-ownership effect in memory. Whereas Westerners display enhanced memory for items owned by the self (vs. mother), this effect is reversed among Asian participants. Developing this line of inquiry, here we considered whether cultural influences on ownership extend to other outcomes-specifically, the efficiency of object categorization. In two experiments, Western and Asian p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 105 publications
(189 reference statements)
3
47
1
8
Order By: Relevance
“…Instead, self-prioritisation has been traced to the operation of a different underlying mechanism—a response bias ( Constable et al, 2019 ). For example, using drift diffusion modelling to identify the processes supporting task performance ( Ratcliff et al, 2016 ; Voss et al, 2013 ; White & Poldrack, 2014 ), Golubickis et al (2018 , 2019 ) demonstrated that the self-ownership effect was underpinned by variability in the evidential requirements of response generation, such that less information was needed to generate owned-by-self compared with owned-by-other decisions. Inter-estingly, no differences in the efficiency of stimulus processing were observed as a function of ownership.…”
Section: Ownership and Decisional Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead, self-prioritisation has been traced to the operation of a different underlying mechanism—a response bias ( Constable et al, 2019 ). For example, using drift diffusion modelling to identify the processes supporting task performance ( Ratcliff et al, 2016 ; Voss et al, 2013 ; White & Poldrack, 2014 ), Golubickis et al (2018 , 2019 ) demonstrated that the self-ownership effect was underpinned by variability in the evidential requirements of response generation, such that less information was needed to generate owned-by-self compared with owned-by-other decisions. Inter-estingly, no differences in the efficiency of stimulus processing were observed as a function of ownership.…”
Section: Ownership and Decisional Processingmentioning
confidence: 99%
“…Indeed, conflict between siblings and peers routinely derives from disputes over proprietorship ( Furby, 1980 ; Ramsey, 1987 ). In Golubickis et al’s (2018 , 2019 ) object-classification task, a response bias is indicative of the operation of an egocentric task-related strategy. That is, repeated interactions with one’s own (vs. other people’s) possessions create a preference for self-relevant responses (i.e., prior experience tunes decisional processing).…”
Section: Ownership and Decisional Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable evidence for ownership advantages in memory (e.g. Cunningham et al, 2008; and some evidence that items designated as self-owned may be perceptually or attentionally prioritised (Truong et al, 2017) or may create a bias in judgement and decision making Golubickis et al, 2018;Golubickis, Ho, Falbén, Mackenzie, et al, 2019). Selfrelevant stimuli (such as owned objects) are also identified and responded to faster than other stimuli (Constable, Rajsic, et al, 2019;Sui et al, 2012;Woźniak et al, 2018;Woźniak & Knoblich, 2019).…”
Section: It Goes With the Territory: Ownership Across Spatial Boundariesmentioning
confidence: 99%